Challenges of Seeking Reproductive Health Care in People Experiencing Intimate Partner Violence - O’Connor-Terry, Carly (Journal of interpersonal violence, 2022)
Title X is a federally funded family planning initiative that provides low-cost and confidential reproductive health services to its clients. In recent years, Title X has been the subject of debate as its core tenants have been revised by the current administration. Though advocates have fought against these changes, the voices of survivors on intimate partner violence are absent from this conversation. This study was designed to elicit the opinions and experiences on survivors of intimate partner violence on reproductive decision-making, their access to care, and their opinions about political efforts to restrict this access. Twenty-six semi-structured interviews were conducted with women who were seeking services for intimate partner violence. These interviews were audio-recorded, transcribed, and coded. Codes were then organized into themes. Participants endorsed the need for confidential services due to experiences of coercion from their partners and the fear of retaliation against them. Participants largely supported accessible contraception but reported the need for contraception to be reliable. Participants addressed pregnancy and its many complexities and advocated for nondirective options-counseling. Overall, participants spoke about their challenges with reproductive health care and their opinions on how best to service survivors of intimate partner violence. This study asserts the need for advocates for survivors to advocate for the preservation of Title X and establishes the need for future studies on the prevalence of intimate partner violence in Title X clinics.